Creating highly reliable health care organisations through reverse exchanges. Issue 3 (28th September 2020) - Kumar, Manisha; Rich, Nicholas; Kumar, Maneesh; Liu, Ying
Abstract : Purpose: This paper aims to explore patient to care provider reverse exchanges to improve the care processes and service supply chain using an online feedback platform. This paper demonstrates how a better understanding of timely and unsolicited feedback ("voice of the patient as a customer") stimulates local interventions to improve service delivery and enact the essential characteristics of highly reliable organisations (HRO). Design/methodology/approach: A realist approach involving an exploratory hospital case study using user feedback from an IT patient feedback platform. The methodology included interviews, secondary data and access to thousands of patient feedback narratives. Findings: The findings show that a systems approach to the supply chain, using real-time feedback to enact process improvement is beneficial and a fruitful source of innovation for professional services staff. The setting of the improvement focusses on a true "voice of the customer" rather than attempting to improve arbitrarily internal process efficiency has major benefits for staff and their engagement with the right interventions to support higher performance. Practical implications: The findings show major positive benefits for the adaptation and constant reflection of staff on the service provided to patients. The approach provides a means of reflecting as to whether the current supply chain and service provision are fit for purpose, as well as reliable, efficient and of value to the consumer. Originality/value: This study is one of a few that adopt the consumer orientation needed to fully exploit the concepts of patient-centric improvement by including dynamic feedback in the supply chain and systems approach to care.